Iranian EFL Young Learners’ Responses to the Implementation of Collaborative and Individual Reading Activities in Reading Sessions - Mania Koohafkan; Faramarz Azizmalayeri; Hossein Ahmadi (Research in English Language Pedagogy, 2022)
This qualitative study investigated EFL young learners’ responses to reading activities in reading sessions. It was an attempt to examine students’ responses towards the implementation of individual and collaborative reading activities in teaching reading as a foreign language in reading sessions. To this purpose, 16 Iranian EFL young learners at a primary bilingual school in Tehran together with their English teachers contributed to the study. They were both randomly selected from available teachers and students in Tehran. The learners were around eight years old. The study lasted for 12 weeks. The method used in this study was qualitative. Teachers’ reflective journals, some participant observations, and face-to-face interviews with teachers were the instruments used in this study. The data elicited from the interview transcripts and observations transcription were analyzed inductively. The narrative analysis of interview transcription was coded into themes. The results indicated that collaborative and individual reading activities in reading sessions have a positive effect on young learners’ reading comprehension. Moreover, the students showed noticeable responses to the implementation of collaborative reading activities in reading sessions.